Correlation between ferritin levels and lipid profile in children with transfusion-dependent thalassemia at Dr Soetomo general hospital, surabaya - Tandirerung, Rivans Jackson; Cahyadi, Andi; Andarsini, Mia Ratwita; Widjaja, Nur Aisiyah (Edelweiss Applied Science and Technology, 2024)
High levels of ferritin and adherence to low iron chelation are associated with the incidence of dyslipidemia. This process potentially causes some harmful effects, such as atherosclerosis. However, the correlation between ferritin level and lipid profile in thalassemia is still widely varied. The aim of this research was conducted to study the relationship between ferritin level and lipid profile. This research was a cross-sectional study involving 35 patients aged 5-18 years, diagnosed with transfusion-dependent thalassemia at Dr Soetomo General Hospital, Surabaya, Indonesia in November 2022. The sample was chosen by a consecutive non-randomized sampling technique. Patients previously diagnosed with dyslipidemia, diabetes mellitus type 1 and 2, metabolic syndrome, and having a history of anti-dyslipidemia medication and corticosteroids were excluded. Data were obtained from the medical record. Subsequently, the blood sample was drawn before the patients received any blood transfusion and examined for ferritin, total cholesterol, LDL, HDL, Triglyceride, apoA, and apoB levels. The data was analysed descriptively and the correlation between ferritin level and lipid profile was analysed statistically using Spearman, Pearson, and Chi-Square. According to the statistical analysis, a significant correlation was found between ferritin and LDL level (p = 0.013; coefficient correlation = 0.414), and total cholesterol (p = 0.006; coefficient correlation = 0.457). Meanwhile, ferritin level was not significantly related to high-density lipoprotein (p = 0.283), triglyceride (p = 0.131), apolipoprotein A (p = 0.83), apolipoprotein B (p = 0.26). Ferritin level was correlated significantly to LDL and total cholesterol level.